Marriage, Relationship Quality, and Sleep among U.S. Older Adults - Chen, Jen-Hao (J Health Soc Behav, 2015)
Sleep is a restorative behavior essential for health. Poor sleep has been linked to adverse health outcomes among older adults, however, we know little about the social processes that affect sleep. Using innovative actigraphy data from the National Social Life, Health and Aging Project (N=727), we considered the role of marriage, positive marital relationship support, and negative marital relationship strain on older adults’ (aged 62–90) self-reported and actigraph-measured sleep characteristics. We found that married older adults had better actigraph-estimated but not self-reported sleep characteristics than the unmarried. However, among the married, those who reported more negative aspects of their marital relationship reported more insomnia symptoms, with the association reduced when psychosocial characteristics were added to the model. The married who reported more positive aspects of their marital relationship showed better actigraph-estimated sleep characteristics; taking characteristics of the physical and mental health and home environment into account reduced this association.